Comparative studies of numerical integration technique as an implemented computer algorithm for simulation of induction machine / Mohd. Azan Omar and Roslan Abdul Rahman - Omar, Mohd. Azan; Abdul Rahman, Roslan (1991)
The objective of- the project is to investigate and analyse various numerical integration technique in term of accuracy and time taken to do a simulation. In addition,analysis are also perform to analyse the performance of an Induction Motor and to predict the system capability and stability. The simulation then carried out based on variation in terminal voltage(p.u) and frequency(Hz). Graphical software are developed by using Turbo Pascal Version 5.5 whereas the output result to be displayed. The graphical output will be in superimposing of four type of voltage,slip,torque and current.